Panel flutter of rotating circular shells in a supersonic gas flow - Bochkarev, Sergey Arkadievich; Matveyenko, Valeriy Pavlovich (Computational Continuum Mechanics, 2008)
A finite element algorithm for panel flutter analysis of rotating circular shells in a supersonic gas flow is developed. The algorithm takes into account the effects of centrifugal, Coriolis and aeroelastic forces. A geometric rigidity matrix evaluating the influence of the initial circumferential force caused by centrifugal forces is constructed during the solution of the static problem. Aerodynamic pressure is calculated using the quasi-static aerodynamic theory. The results of the solution to the problem of shells with varying geometric parameters and under different boundary conditions are given. It is shown that in the case of specific geometric parameters, the rotation of the shell leads to a decrease in the aeroelastic stability boundary.